Hepatitis E Virus Genotype 3 among Hemodialysis Patients in Mexico: First Identification of Chronic Infection - Edgar D. Copado-Villagrana; Ilsy X. Duarte-López; Arturo Calderón-Flores; Isidro Loera-Robles; Oliver Viera-Segura; Nora A. Fierro (Pathogens, 2024)
The global distribution of hepatitis E virus (HEV) is attributed to its capacity to spread through several routes of transmission; hemodialysis has gained increased amounts of attention in recent years. Although Mexico is considered a hyperendemic region for hepatitis E, no HEV surveillance is performed in the country. The frequency of HEV in hemodialysis (HD) patients has not been determined. Herein, we conducted a cross-sectional single-center analytical study including 67 serum samples from HD patients. Anti-HEV IgG and IgM antibodies and the viral genome were determined; partial regions within the HEV genome were sequenced for further phylogenetic analysis. Globally, 14.9% of the tested patients exhibited reactivity for IgG antibodies against HEV, and none showed reactivity to IgM. A total of 5.9% of the samples showed HEV genome amplification, and sequencing confirmed the identity of genotype 3; subsequent analysis of positive cases revealed two acute cases and chronic hepatitis E infection in one patient. Notably, the chronic patient was negative for anti-HEV IgG antibodies. Our findings highlight the importance of viral genome testing in HD patients and the need to establish guidelines for HEV detection in Mexico.